Spectrum of Isolates and Antimicrobial Susceptibility Pattern from Blood Cultures in Tertiary Care Hospital, Riyadh - Fizza Khalid; Christy Poulose; Azza Elsheikh; Abid Mahmood; Osamah T. Khojah (Journal of Pure and Applied Microbiology)
Clinical presentation of bloodstream infection ranges from transitory bacteremia to fulminant septic shock with substantial mortality. Regular monitoring of bacteremia etiology helps rationalize therapy, revealing the spectrum of bacterial infections and their sensitivity pattern in a particular area. In this study, we investigated the prevalence and antimicrobial susceptibility profile of all bacterial pathogens isolated from blood cultures in a tertiary care hospital in Riyadh, Saudi Arabia. It was a retrospective study and data was collected over a period of one year from January 2022 to December 2022, with a total of 3,429 blood cultures requested. Culture positivity was found in 5% of suspected bacteremia cases, with a slight male predominance. Gram-positive bacteremia was 57%, mainly isolated from male patients. Methicillin-resistant Staphylococcus aureus (MRSA) was found in 38% of total Staphylococcus aureus (S. aureus) bacteremia cases, with all Gram-positive isolates susceptible to vancomycin and linezolid. Escherichia coli (E. coli) was the most common Gram-negative bacteria, while Pseudomonas and Stenotrophomonas species were the main non-fermenting pathogens, accounting for 66.7% of cases. Extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae accounts for 17.5% in total with the highest production in Proteus species, whereas 75% of Pseudomonas species were carbapenamase producers. Consequently, the prevalence of multidrug-resistance microorganisms in critically ill individuals may account as a significant threat in hospital settings. Continuous monitoring is essential for comprehending the prevalence of bacteremia and their susceptibility pattern to create successful empirical therapy options and antimicrobial stewardship.